Hyperpolarized 83Kr magnetic resonance imaging of alveolar degradation in a rat model of emphysema - Lilburn, David M.L.; Lesbats, Clémentine; Six, Joseph S.; Dubuis, Eric; Yew-Booth, Liang; Shaw, Dominick E.; Belvisi, Maria G.; Birrell, Mark A.; Pavlovskaya, Galina E.; Meersmann, Thomas (The Royal Society, 2015)
Hyperpolarized 83Kr surface quadrupolar relaxation (SQUARE) generates MRI contrast that was previously shown to correlate to surface to volume ratios in porous model surface systems. The underlying physics of SQUARE contrast is conceptually different from any other current MRI methodology as the method utilizes the nuclear electric properties of the spin I = 9/2 isotope 83Kr. To explore the usage of this non-radioactive isotope for pulmonary pathophysiology, MRI SQUARE contrast was acquired in excised rat lungs obtained from an elastase induced model of emphysema. A significant 83Kr T1 relaxation time increase in the SQUARE contrast was found in the elastase treated lungs compared to the baseline data from control lungs. The SQUARE contrast suggests a reduction in pulmonary surface to volume ratio in the emphysema model that was validated by histology. The finding supports usage of 83Kr SQUARE as new biomarker for surface to volume ratio changes in emphysema.